Impact of Emergency Colectomy on Survival of Patients With Fulminant Clostridium difficile Colitis During an Epidemic Caused by a Hypervirulent Strain - Lamontagne, François (2007)
OBJECTIVES: To determine whether emergency colectomy reduces mortality in patients with fulminant Clostridium difficile-associated disease (CDAD), and to identify subgroups of patients more likely to benefit from the procedure. SUMMARY BACKGROUND DATA: Many hospitals in Quebec, Canada, have noted since 2003 a dramatic increase in CDAD incidence and in the proportion of cases severe enough to require intensive care unit (ICU) admission. The decision to perform an emergency colectomy remains largely empirical. METHODS: Retrospective observational cohort study of 165 cases of CDAD that required ICU admission or prolongation of ICU stay between January 2003 and June 2005 in 2 tertiary care hospitals of Quebec. Multivariate analysis was performed through logistic regression; adjusted odds ratios (AOR) and their 95% confidence intervals (CI) were calculated. The primary outcome was mortality within 30 days of ICU admission. RESULTS: Eighty-seven (53%) cases resulted in death within 30 days of ICU admission, almost half (38 of 87, 44%) within 48 hours of ICU admission. The independent predictors of 30-day mortality were: leukocytosis ≥50 × 10(9)/L (AOR, 18.6; 95% CI, 3.7–94.7), lactate ≥5 mmol/L (AOR, 12.4; 95% CI, 2.4–63.7), age ≥75 years (AOR, 6.5; 95% CI, 1.7–24.3), immunosuppression (AOR, 7.9; 95% CI, 2.3–27.2) and shock requiring vasopressors (AOR, 3.4; 95% CI, 1.3–8.7). After adjustment for these confounders, patients who had an emergency colectomy were less likely to die (AOR, 0.22; 95% CI, 0.07–0.67, P = 0.008) than those treated medically. Colectomy seemed more beneficial in patients aged 65 years or more, in those immunocompetent, those with a leukocytosis ≥20 × 10(9)/L or lactate between 2.2 and 4.9 mmol/L. CONCLUSION: Emergency colectomy reduces mortality in some patients with fulminant CDAD.